Parental Communication Through Conversation Orientation in Preacher Families - Ismail, Safinah; Rasit, Rosmawati Mohammad; Aini, Zulkefli (International Journal of Psychosocial Rehabilitation, 2020)
A family with strained relationships and the occurence of conflicts due to poor communication among each other. Therefore, conversation orientation is important to encourage every family member to have a discussion. It is one of the orientations in the family communication pattern developed by Ritchie & Fitzpatrick. Conversation orientation is a condition that encourages each family member to engage freely in interactions that involve various topics of discussion. Therefore, the aim of this study was to examine family communication through the conversation orientation adopted by parents in the preacher's family. A qualitative approach in the form of phenomenology was used in this study based on the phenomena involved. Qualitative data were collected through a semi-structured interview protocol. In-depth interviews were conducted with three preacher families consisting of parents who served as primary data, while children and personal helpers served as support data. The analysis of the study using thematic analysis and ti atlas. This study found that parents in the preacher's family have applied family communication through conversation orientation when communicating with children from the aspects of bilateral interaction, openness, cooperation and togetherness. They talk about making decisions, executing management and so on. They provide high levels of cooperation in children's activities and contribute to children's academic achievement. In this regard, the practice of praise can even touch the emotions and make a deep impression on the children. As well as the love and care provided by parents in the preacher's family, they make the children a friend and the closeness makes it easy for children to share problems with their parents.